Seaweed dryer design criteria assessment using analytic hierarchy process - Lim, Nino Rigo Emil G. (Animo Repository, 2017)
© 2017 IEEE. Drying is an integral part of seaweed manufacturing process. The Philippines is one of the leading producers of seaweeds in the world. However, due to the lack of development of appropriate technologies, the country is struggling to compete with the quality of seaweed produced internationally. A significant amount of local seaweed farmers in the Philippines are still using the traditional sun drying method for seaweeds drying. Due to the apparent dependence on this drying method from a single unreliable source, the quality of seaweeds produced and the capacity of the manufacturing process can be affected by abrupt changes in climatic conditions. Hence a seaweed dryer becomes necessary to improve the quality and quantity of seaweeds produced. However, in designing an appropriate seaweed dryer, various potentially-conflicting criteria are needed to be considered simultaneously. In this study, the analytic hierarchy process was proposed to evaluate the important factors and considerations in designing a seaweed dryer. The results of the study revealed several implications that should be considered when designing a seaweed dryer to be of optimal benefit to the Filipino stakeholders and farmers.